Molecular cloning of a cyclodextrin glucanotransferase gene from alkalophilic Bacillus sp. TS1-1 and characterization of the recombinant enzyme - Rahman, Kamalesh; Mohd Illias, Rosli; Hassan, Osman; Nik Mahmood, Nik Azmi; Abdul Rashid, Noor Aini (Elsevier Inc., 2006)
A cyclodextrin glucanotransferase (CGTase) gene from Bacillus sp. TS1-1 was isolated and cloned into Escherichia coli. Starting from TTG codon, there was an open reading frame composed of 2163 bp (721 amino acids). The NH2 terminal position encoded a 46-amino acid of a signal peptide and followed by the mature enzyme (675 amino acids). The deduced amino acid sequence of the mature CGTase from Bacillus sp. TS1-1 exhibited 98.7% homology with 96% identity to the CGTase sequence from alkalophilic Bacillus sp. 1-1. The recombinant CGTase of Bacillus sp.TS1-1 expressed in E. coli was successfully purified to homogeneity using ammonium sulfate precipitation, followed by alpha-cyclodextrin-bound epoxy- activated Sepharose 6B affinity chromatography. The purified CGTase enzymes exhibited a single band with molecular weight of 75 kDa on SDS-PAGE. Biochemical characterization of the enzyme shows an optimum temperature of 60 ◦C and optimum pH of 6.0. The enzyme was stable between pH 7 and 9 and temperature up to 70 ◦C. The Km and Vmax values calculated were 0.52 mg/ml and 54.35 mg of beta-cyclodextrin/ml/min. The yield of the products from soluble starch as the substrate were 86% for gamma-cyclodextrin and 14% for -cyclodextrin after 24 h incubation at 60 ◦C, without adding any selective agent. The total beta-CD produced under the conditions mentioned above was 3.65 g/l.